2014
DOI: 10.1177/0194599814541627a306
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Crosslinked Hyaluronic Acid Hydrogel (PureRegen Gel Sinus) in Ethmoidectomy: A Randomized, Controlled Trial

Abstract: Oral Presentations P127Objectives: (1) Assess secondary nasoseptal flaps (NSF) as a viable reconstructive option. (2) Evaluate postoperative vascularity of secondary NSFs. (3) Compare cerebrospinal fluid (CSF) leaks and complication rates of secondary NSFs to primary NSFs.Methods: This is a retrospective review of patients from 2009 to 2013 undergoing transsellar approaches for skull base tumors at the University of Pittsburgh Medical Center. In cases where the necessity of a vascularized reconstructive flap w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In a bowel anastomotic rat model, application of NCH gel significantly improved tissue healing (unpublished data). A gel similar to NCH also has been reported to significantly improve wound healing (i.e., mucosa reepithelialization) after endoscopic sinus surgery in both animal and clinical studies [22,23,50].…”
Section: Discussionmentioning
confidence: 98%
“…In a bowel anastomotic rat model, application of NCH gel significantly improved tissue healing (unpublished data). A gel similar to NCH also has been reported to significantly improve wound healing (i.e., mucosa reepithelialization) after endoscopic sinus surgery in both animal and clinical studies [22,23,50].…”
Section: Discussionmentioning
confidence: 98%
“…Merogel, an esterified hyaluronan derivative, lasts longer than hyaluronan and can easily be used in a non-woven sponge preparation. In the past, merogel has been successfully used as an anti-adhesive packing agent to stimulate mucosal epithelial healing in functional endoscopic sinus surgery [28] . Moreover, in earlier studies, we demonstrated that supplementary use of Merogel enhances the success of En-DCR surgery for primary chronic dacryocystitis via promotion of early osteium reepithelialization, suppression of fibrotic tissue development at the ostium, and prevention of the lacrimal sac apposition to the nasal mucosa flaps [15,[29][30] .…”
Section: Discussionmentioning
confidence: 99%